Development and validation of a new set of indicators to assess the quality of maternal and child nutritional care at the primary care - Ancira-Moreno, Monica; Omaña-Guzmán, Isabel; Bautista-Morales, Arturo Cuauhtémoc; Acosta-Ruiz, Omar; Hernández Cordero, Sonia; Burrola-Méndez, Soraya; Vilar-Compte, Mireya; Monterrubio Flores, Eric; Kaufer-Horwitz, Martha; Pérez Navarro, Cecilia; Muñoz-Manrique, Cinthya; Mazariegos, Mónica; et al. (Frontiers in Medicine, 2022)
Maternal and child malnutrition is a worldwide public health problem with short, medium, and long-term adverse consequences for both mother and child. In Mexico, maternal and child malnutrition represents a serious public health problem that must be urgently addressed. In this context, Primary Health Care (PHC) plays an important role in the prevention, detection, monitoring, and treatment of the different forms of maternal and child malnutrition. Assessing the quality of nutritional care offered at this level of care is necessary in order to improve it; however, there are no indicators for the evaluation of this quality. Therefore, this study aimed at developing a set of indicators to assess the quality of maternal and child nutritional care at PHC. We developed indicators for different stages of life: preconception, pregnancy, infancy, and preschool age. A systematic review of the literature on clinical guidelines for the prevention, diagnosis, and treatment of the different forms of malnutrition was carried out; the recommendations of the guidelines evaluated with good quality were extracted. Based on these recommendations, 22 indicators were constructed. A pilot study was carried out to validate the indicators and 16 indicators were selected to assess the maternal and child nutritional care at PHC.